North Korea's nuclear revelation puts spotlight on China. - Jen Lin-Liu (IEEE spectrum)
When North Korea admitted in mid-October that it had been actively developing nuclear weapons, in violation of international agreements, it put several big diplomatic players in awkward positions: the United States, because it wanted to keep the focus on Iraq; Japan, which was eager to keep improving relations with the Koreas; but most of all China, nominally an ally of North Korea, but with plenty of good reasons to be unhappy with the prospect of its erratic neighbor's acquiring weapons of mass destruction. On the surface, relations between Asia's two Communist countries still seemed cozy at the time the United States confronted North Korea with intelligence on the latter's clandestine nuclear program. But in fact, the fast-industrializing People's Republic has had less and less in common with its mostly pre-modern neighbor. So it is perhaps no wonder that China seized on Pyongyang's surprise admission as an opportunity to improve its relationship with the United States.